Non-human Primate Models to Investigate Mechanisms of Infection-Associated Fetal and Pediatric Injury, Teratogenesis and Stillbirth - Li, Miranda; Brokaw, Alyssa; Furuta, Anna M.; Coler, Brahm; Obregon-Perko, Veronica; Chahroudi, Ann; Wang, Hsuan-Yuan; Permar, Sallie R.; Hotchkiss, Charlotte E.; Golos, Thaddeus G.; Rajagopal, Lakshmi; Adams Waldorf, Kristina M. (Frontiers in Genetics, 2021)
A wide array of pathogens has the potential to injure the fetus and induce teratogenesis, the process by which mutations in fetal somatic cells lead to congenital malformations. Rubella virus was the first infectious disease to be linked to congenital malformations due to an infection in pregnancy, which can include congenital cataracts, microcephaly, hearing impairment and congenital heart disease. Currently, human cytomegalovirus (HCMV) is the leading infectious cause of congenital malformations globally, affecting 1 in every 200 infants. However, our knowledge of teratogenic viruses and pathogens is far from complete. New emerging infectious diseases may induce teratogenesis, similar to Zika virus (ZIKV) that caused a global pandemic in 2016-2017; thousands of neonates were born with congenital microcephaly due to ZIKV exposure in utero, which also included a spectrum of injuries to the brain, eyes and spinal cord. In addition to congenital anomalies, permanent injury to fetal and neonatal organs, preterm birth, stillbirth and spontaneous abortion are known consequences of a broader group of infectious diseases including group B Streptococcus (GBS), Listeria monocytogenes, Influenza A virus (IAV) and Human Immunodeficiency Virus (HIV). Animal models are crucial for determining the mechanism of how these various infectious diseases induce teratogenesis or organ injury, as well as testing novel therapeutics for fetal or neonatal protection. Other mammalian models differ in many respects from human pregnancy including placentation, labor physiology, reproductive tract anatomy, timeline of fetal development and reproductive toxicology. In contrast, nonhuman primates (NHP) most closely resemble human pregnancy and exhibit key similarities that make them ideal for research to discover the mechanisms of injury and for testing vaccines and therapeutics to prevent teratogenesis, fetal and neonatal injury and adverse pregnancy outcomes (e.g., stillbirth or spontaneous abortion). In this review, we emphasize key contributions of the NHP model pre-clinical research for ZIKV, HCMV, HIV, IAV, L. monocytogenes, Ureaplasma species, and GBS. This work represents the foundation for development and testing of preventative and therapeutic strategies to inhibit infectious injury of human fetuses and neonates.